Unexpected varus deformity and concomitant metal ion release and MRI findings of modular-neck hip stems: descriptive RSA study in 75 hips with 8 years’ follow-up - Kiernan, Sverrir; Kaptein, Bart; Flivik, Carl; Sundberg, Martin; Flivik, Gunnar (Acta Orthopaedica, 2020)
Background and purpose — Modular-neck hip stems have been identified with corrosion-related problems from the neck–stem junction. We report an ongoing varus deformity of modular-neck hip stems with simultaneous metal ion release observed during a study comparing the migration of modular vs. standard hip stems. Patients and methods — We followed 50 patients with modular and 25 with standard neck stems using radiostereometry (RSA). At 5- year follow-up, we noted a compromised integrity of the modular stem with varus deformity in the neck–stem interface. Changes in head–tip distance as well as whole-blood ion concentration and MRI findings were analyzed. The modular stems were followed further up to 8 years. Results — The head–tip distance decreased continuously by 0.15 mm per year resulting in 1.2 (95% CI 1.0–1.4) mm at 8 years for modular stems, while for the standard stems at 5 years, the decrease was 0.09 (CI 0.0–0.2) mm or 0.02mm/year. For the modular stems, the reduction in head–tip distance correlated to the increase in whole-blood cobalt concentration at 8 years but not to the MRI grading of tissue reactions. At 5 years, cobalt levels were 4.9 μg/L for modular stems and at 8 years 4.8 μg/L, whereas for standard stems this was 1.0 μg/L. After 8 years, 9 of 72 stems had been revised for different reasons, but only 1 with obvious adverse local tissue reaction (ALTR). Interpretation — We present a surprisingly large progressive deformation at the modular neck–stem junction, but so far without a definite clinical problem. Even the femoral head seems to show slight compression onto the taper over time. A high rate of revisions for the modular type of this stem has raised general concerns, and it has been recalled from the market.